TRADITIONAL CARPETS AND CARPETS IN DAILY LIFE AND RITUALS OF THE KYRGYZ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the traditional art of carpeting is considered as a decorative and applied art that reflects the ethno-culture of the Kyrgyz people for several centuries. It was noted that traditional carpets and carpet products occupy a significant place in the semi-nomadic life of Kyrgyz people and are used as necessary items. Certain features of the nomadic economy had an impact on the development of carpeting. However, due to the poor condition of the land and the lack of water during the drought, a significant number of farmers were forced to engage in certain crafts in search of income. The nature of women’s work and agricultural work was influenced by the development of carpeting. At this time, Kyrgyz women had the opportunity to focus more on weaving carpets and carpet products. For a long time, Kyrgyz carpets were not made for sale. The range of application of carpets and carpet products is wide. It was widely used, mainly as an object in personal life, as a means of warming houses, in the household, at traditional weddings and funeral rituals.
Keywords: Kyrgyz, traditional carpets and carpet products, nomadic culture, scope of use of carpet products, women, carpet weaving